加拿大海盆氟氯烃的分布及其示踪研究 - 孙娜; 李文权 (2006)
中国第二次北极科学考察期间(2003年7—9月)于加拿大海盆采集了9个站位的水样,用于氟氯烃(CFCs)的分析。结果表明加拿大海盆表层水中的CFC-11浓度最高为6.70pmol/kg,CCl4浓度最高为9.62pmol/kg,但均未达到饱和状态。二者在表层水中的饱和度分别在70.54%—84.70%和76.54%—91.53%之间,这可能与海冰覆盖和低CFCs浓度的太平洋水的入侵有关。在2000m深度仍存在相当浓度的氟氯烃,这表明加拿大海盆深层水与外界水体存在交换更新。氟氯烃的垂直分布进一步证实了加拿大海盆水团呈层状的垂直分布结构。同时采用pCFC-11、pCCl4测年法对各水团年龄进行了估算。 Seawater samples at 9 stations were collected in the Canada Basin during the Second Arctic Scientific Expedition of China (from Jul. to Sep.,2003). The result of chlorofluorocarbons(CFCs)determination showed that the highest concentration of CFC-11 and CCl_4 in the surface water are 6.7 pmol/kg and 9.62 pmol/kg respectively, but they are all undersaturated. The degrees of saturation of CFC-11 in the surface water lies in the range of 70.54% to 84.70% , and that of CCl_4 within 76.54% to 91.53% , probably caused by local ice cover and the invasion of the Pacific water with low CFC concentration. The significant concentration of CFCs at the depth of 2000 m indicated that deep water in the Canada Basin was exchanged and replaced with the open seawater outside. The vertical distributions of CFCs confirmed that the water masses in the Canada Basin were stratified. The method of pCFC-11 and pCCl_4 dating are used to evaluate the apparent ages of water masses. 国家自然科学基金项目(40276035)资助。